The efficacy of physiotherapy in the inclusion of physically deficient children in regular schools: a literature review - Durce, Karina; SantAnna Ferreira, Claudia Adriana; Souza Pereira, Priscila; Balbino Souza, Brenda (O Mundo da Saúde, 2006)
This study aims to show aspects of school inclusion of deficient children and ways the physiotherapist as part of a multidis- ciplinary team can effectively do her work in this process. In 1994, in Salamanca, Spain, UNESCO held the World Conference on Special Needs Education: Access and Quality which proposed an equalitarian and non-excluding education, classifying as an obligation of governments the insertion of these children in the regular system of education. It is clear that the access of deficient children in regular schools is free by law, and for this reason schools have to present themselves as inclusive contexts, that is, they must be prepared to receive all pupils. The work of an interdisciplinary team composed by educators, doctors, occupational therapists, psychologists and physiotherapists inside schools is crucial. Physiotherapists have as their role to enhance the techniques of existing helping resources in physiotherapy one can use to minimize the difficulties of persons with physical deficiencies. By means of special techniques and the adaptation of equipment and furniture, one can create conditions for a better adaptation, performance and opportunities for deficient children as regards the development of their capacities and sharing experiences.